2019
DOI: 10.1007/s13762-019-02425-0
|View full text |Cite
|
Sign up to set email alerts
|

Recuperation patterns in fish with reference to recovery of erythrocytes in Barbonymus gonionotus disordered by an organophosphate

Abstract: Organophosphate pesticides are extravagantly used in worldwide context to get rid of insects. Due to their relevance and edges in agriculture, organophosphate pesticide can effortlessly stretch to the aquatic ecological units and, correspondingly, cause threats to aquatic animals, like fish. Profenofos could be a diligent and cytotoxic organophosphate pesticide. Animals become liable to profenofos by means of water and food. Present experiment determines toxicological impacts of profenofos through the in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In this research when Labeo rohita was treated with PPF, different morphological changes were observed including the pear-shaped nucleus, in different cells, and in some cases, bilobed nucleus like in erythrocyte micronucleus was observed like in red blood cells and in white blood cell types. While in the earlier report, the greater strength of nuclear anomalies including nuclear aberrations of erythrocyte, micronucleus, terminal nucleus, extended and swollen nucleus, and karyopyknotic was observed in silver barb (Barbonymus gonionotus) [39] treated with various concentrations of the toxicant. Previously, swollen erythrocytes identified as "spherocytes" change in size and shape of cells like elongated cells, cells with tapered ends, numerous spherocytes, erythrocytes showing contraction from one side and with small projections, the disrupted lipid membrane, and increased lipid peroxidation altered shapes of red blood cells in Ctenopharyngodon idellus [1,40] exposed to the toxicant.…”
Section: Discussionmentioning
confidence: 74%
“…In this research when Labeo rohita was treated with PPF, different morphological changes were observed including the pear-shaped nucleus, in different cells, and in some cases, bilobed nucleus like in erythrocyte micronucleus was observed like in red blood cells and in white blood cell types. While in the earlier report, the greater strength of nuclear anomalies including nuclear aberrations of erythrocyte, micronucleus, terminal nucleus, extended and swollen nucleus, and karyopyknotic was observed in silver barb (Barbonymus gonionotus) [39] treated with various concentrations of the toxicant. Previously, swollen erythrocytes identified as "spherocytes" change in size and shape of cells like elongated cells, cells with tapered ends, numerous spherocytes, erythrocytes showing contraction from one side and with small projections, the disrupted lipid membrane, and increased lipid peroxidation altered shapes of red blood cells in Ctenopharyngodon idellus [1,40] exposed to the toxicant.…”
Section: Discussionmentioning
confidence: 74%
“…In our findings, an increment in the frequency of micronuclei in silver barb's erythrocyte was explicit after 28-day exposure of pesticide on concentration and duration of exposure of malathion. The incidence of micronuclei (genome damage events) generation is a biomarker of genotoxic events and chromosomal instability or damage [ 28 ] and could intensify the risk of developmental and degenerative diseases in fish following exposure to cytotoxic and/or genotoxic agents [ 29 , 30 ]. Micronuclei were also investigated to initiate during chromatid fragments caused by the disrepair of DNA breaks or anaphase from a lagging acentric chromosome or unrepaired DNA breaks [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Karyorrehexic is characterized by the destruction of the cell nucleus causing it to loses its original shape and form scattered chromatin fragments. Karyolysis is characterized by a very pale, and shapeless cell nucleus (Abdelhalim & Jarrar, 2011;Islam, et al, 2019). Treatment groups T1, T2, and T3 showed in the nice had necrotic.…”
Section: Discussionmentioning
confidence: 99%